Parenting Stress and Hypertension in Parents of Mental Retardation Children - Kamerawati, Choni; Prasetyowati, Irma; Ariyanto, Yunus (Unnes Journal of Public Health, 2018)
Abstract   Parents with mental retardation children experience higher parenting stress than parents with other types of disability. Differences in responses to stressors indicate a level of parenting stress that is influenced by the characteristics of children, family, parents, and the environment. Parenting stress that is not managed and occurs in a long time can cause physical disorders of hypertension. The purpose of this study was to describe the parenting stress and the incidence of hypertension in the parents of children with mental retardation aged 12-15 years. This research is a descriptive research with quantitative approach. The sample of this study was the father and mother of mental retardation  students aged 12-15 years of 59 respondents who met the criteria of inclusion and exclusion. The result of this research is most of the hypertension respondent have high parenting stress level of 53,6% in fathers and 64,5% in mothers.   Keywords: hypertension, mental retardation, parenting stress, parents.     Abstrak   Orang tua dengan anak retardasi mental cenderung mengalami parenting stress tinggi dibandingkan orang tua dengan anak jenis kecacatan lain. Adanya perbedaan tanggapan terhadap stressor menunjukkan adanya tingkatan parenting stress yang dipengaruhi oleh karakteristik anak, keluarga, orang tua, dan lingkungan. Parenting stress yang tidak dikelola dan tejadi dalam waktu lama terjadi dapat menyebabkan gangguan fisik hipertensi. Tujuan penelitian ini adalah menggambarkan parenting stress dan kejadian hipertensi pada orang tua yang mengasuh anak retardasi mental usia 12-15 tahun. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Sampel penelitian ini adalah ayah dan ibu siswa retardasi mental usia 12 – 15 tahun sebesar 59 responden yang memenuhi kriteria inklusi dan eksklusi. Hasil dari penelitian ini adalah sebagian besar responden hipertensi mengalami tingkat parenting stress tinggi sebesar 53.6 % pada ayah dan 64.5 % pada ibu.  Kata kunci: hipertensi, orang tua, parenting Stress, retardasi mental.